BELIEFS ABOUT MEDICATIONS IN PATIENTS WITH RHEUMATOID ARTHRITIS AT HANOI MEDICAL UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Rheumatoid arthritis (RA) is a chronic joint disease requiring long-term treatment; therefore, assessing patients’ beliefs about medicines can help predict treatment adherence.Objective: To describe medication beliefs and identify related factors among patients with rheumatoid arthritis (RA) at the Department of Rheumatology, Hanoi Medical University Hospital.Methods: A cross-sectional study was conducted on 142 RA inpatients at the Department of Rheumatology, Hanoi Medical University Hospital from October 2024 to April 2025. Medication beliefs were assessed using the Beliefs about Medicines Questionnaire (BMQ), consisting of two subscales: BMQ - Necessity and BMQ - Concerns.Results: Patients showed a high level of belief in the necessity of their medications (BMQ–Necessity: 19.44 ± 2.26), while also expressing concerns about medication use (BMQ–Concerns: 18.45 ± 2.03). Lower BMQ–Necessity scores were observed among patients living in rural areas, with only secondary education, disease duration ≤ 1 year, seronegative status, moderate-to-high disease activity, and no use of biologic agents (p < 0.05). Conversely, higher BMQ–Concerns scores were found among patients living in rural areas, aged > 60 years, with disease duration ≤ 1 year, moderate-to-high disease activity, and not using biologic agents (p < 0.05).Conclusion: Most RA patients believed in the necessity of their medications but also harbored concerns about their use. In clinical practice, comprehensive counseling and intervention strategies are needed to strengthen beliefs and reduce concerns, thereby improving treatment adherence.
Keywords: Rheumatoid arthritis; beliefs about medications; Hanoi Medical University Hospital